THE IMPLEMENTATION OF CHARACTER EDUCATION IN “SENI KARAWITAN (SEKAR)” EXTRACURRICULAR ACTIVITIES IN SD NEGERI KAUMAN - Oktavia Fitriani; Isnaini Isnaini; Uswatun Hasanah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
This research is aimed to describe the implementation of character educationin the “Seni Karawitan (Sekar)” extracurricular activity in Kauman State ElementarySchool. The study used a descriptive qualitative method. This research was conductedby using an observation technique. The students who joined the Seni Karawitan extracurricularactivity were observed. Character education is implemented in that activity.The steps in this research include finding the problem, formulating the hypothesis,collecting the relevant data, analyzing the data, and testing the hypothesis. The resultsof this study show the character education is implemented in the Seni Karawitanextracurricular activity as an effort to grow the character in the young age. The implementationis done through the attitudes and actions that have to be performed by thestudents when they play gamelan and sang Javanese songs. Seni Karawitan has thevalues of togetherness, leadership, patience, responsibility, politeness, loving the culture,religiousity, gentleness, honesty, discipline, model, concentration, tolerance,happiness, and education. The values reflect the characters that have to be preservedand respected in the daily life. The students of Kauman State Elementary School aremore focused on some values, namely togetherness, patience, leadership, politeness,loving the culture, and responsibility.